The Community Perceptions of Poverty in Gampong Ayon, Seulimeum Sub-district, Aceh Besar Regency (Research Results on March 2017) - Ismail Ismail; Salahuddin Salahuddin; Fuady Fuady (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This paper wants to analyze The Community Perceptions of Poverty in Gampong Ayon, Seulimeum Sub-district, Aceh Besar Regency (Research Results on March 2017) by using descriptive qualitative method. The result shows that Community perceptions of poverty at Gampong Ayon, Seulimeum Subdistrict, Aceh Besar Regency were very diverse, some were positive, some were pessimistic or negative. A positive view, for example, considers poverty as a part of the life of the people in Gampong Ayon that is not used as a burden, while those who have a negative view of poverty occur in Gampong Ayon because of the lack of concern from the government.